Using Fresnel Zone to Characterise and Image Different Types of Diffractors in Low S/N Situations - Bona, Andrej; Pevzner, Roman (2015)
We investigate the possibility to image and characterise the different types of diffractors – such as point, line, and edge – and separate them from reflections by limiting the aperture around the tangent point between the diffraction hyperbola and the relfection traveltime surface. To this end, we look at the tangents of the diffraction hyperbola with typical traveltime surfaces corresponding to the different diffrator types. We do this by studying the coherency of the recorded wavefield along the diffraction hyperbolae. The different types of diffractors show different energy distributions that can be used to characterise the diffractors and separate them from specular reflections. These areas of high energy correspond to the Fresnel zones of the particular diffractor type. Limiting the aperture of the diffraction hyperbola to the particular Fresnel zone results in improvement in S/N, while omitting the Fresnel zone corresponding to the reflections allows for imaging of the diffractors, which have larger Fresnels zones.